Development of an Eco-Pedagogy-Based Islamic Education Curriculum for Inclusive Education of Childhood Cancer Survivors at Sekolah-Ku YKAKI Yogyakarta - Muhammad Saefullah; Satria Kharimul Qolbi (UIN Sunan Gunung Djati Bandung, 2026)
This study originated from the urgent need to provide relevant Islamic Religious Education (PAI) learning for childhood cancer survivors at Sekolah-ku YKAKI Yogyakarta, who study under vulnerable physical, psychological, and social conditions during long-term therapy. The current national PAI curriculum, which emphasises memorisation, is considered incompatible with their needs for more flexible, empathetic, and experiential learning. This study aims to develop an initial design for an inclusive eco-pedagogy-based PAI curriculum that integrates Islamic spiritual values with ecological awareness while accommodating students’ limited physical stamina, fluctuating energy, and constrained study time. A descriptive qualitative approach with an embedded case study design was employed, involving semi-structured interviews with teachers, students, and parents, classroom observations, and document analysis. Data were analysed using Miles and Huberman's interactive model, including data condensation, display, and conclusion drawing, supported by source and method triangulation. The findings reveal five main challenges in PAI learning at YKAKI: fluctuating physical and emotional conditions, limited study time due to therapy schedules, restricted space and infection control measures, lack of varied media and activities, and misalignment between the national curriculum and the children's special needs. In response, an initial eco-pedagogy-based PAI curriculum was formulated with five core principles: spiritual-ecological, flexible-individual, humanistic-empathetic, experiential, and collaborative-community-oriented. This curriculum positions learning as a healing educational space that fosters spirituality, ecological care, and educational continuity for childhood cancer survivors.